Reconstruction of the Intranasal Lining - Zenga, Joseph; Chi, John J. (Facial Plastic Surgery, 2017)
Reconstruction of full-thickness nasal defects has been the subject of surgical inquiry and innovation for over 2,000 years. The replacement of the internal nasal lining is a critical feature of complex nasal reconstruction. Successful reconstruction can prevent cicatricial contraction, external distortion, and internal stenosis. An array of reconstructive possibilities has been described, including cutaneous, mucosal, and fascial options. The challenge to the reconstructive surgeon is to select the repair that maximizes internal stability, while maintaining a patent nasal airway, minimizing morbidity, and meeting patient expectations. This article reviews the options available for the reconstruction of the intranasal lining.
Keywords: nasal reconstruction; internal nasal lining; facial reconstruction; nasal mucosal flap; forehead flap